The Association Between Heart Rate Variability and Sleep Quality - a Narrative Review - Kapica, Marcin; Kopacz, Wojciech; Głogowska, Karen; Wojtas, Mikołaj; Krzyżanowska, Maria; Nowak, Gabriela; Żmijewska, Aleksandra; Sztybór, Mateusz; Maleszewska, Monika; Piątkiewicz, Julia (Journal of Education, Health and Sport, 2024)
Introduction Heart rate variability (HRV) serves as a non-invasive marker to assess autonomic nervous system (ANS) modulation on cardiac rhythm. Its link with sleep quality, particularly in the context of insomnia, posits HRV as a potential indicator of autonomic state variations during sleep disturbances. The prevalence of insomnia, affecting up to 20% of the general population, emphasizes the need to understand its extensive impact. Material and Methods For this review - 41 relevant titles from 1985 to 2024 were selected Analysis of the Literature: Recent studies highlight a bidirectional relationship between insomnia and ANS function, with increased sympathetic activity indicated by physiological and subjective measures in individuals with insomnia. The role of medications like beta-blockers in disrupting ANS and leading to sleep deprivation further connects measurable and perceived aspects of sleep quality, impacting health negatively. Moreover, HRV’s application has expanded beyond professional athletics to daily activity and sleep quality monitoring by the general population, emphasizing its potential in evaluating stress and training intensity. Conclusion: The complex interplay between HRV, insomnia, and health outcomes necessitates further research. However, integrating HRV measurements into clinical and everyday monitoring may offer a promising avenue for improving sleep disorder management and enhancing quality of life.